Literatur Review : Pengelolaan Assembling Rekam Medis Rawat Inap di Rumah Sakit - Noor Yulia; Erviana, Erviana; Laela Indawati; Muniroh, Muniroh (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Assembling is an important part of medical records to examine the correctness of recording, control the use of medical record numbers and control the use of medical record forms. In order for assembling to be carried out well, the medical records unit creates Standard Operating Procedures (SOP) for the assembling section and medical records officers managing assembling must follow the SOP. The aim of the research is to find out the management of assembling inpatient medical records in hospitals using the Literature Review method or also called Narrative Review by collecting several journals using the Bolean System from the Google Scholar Database, to identify and conclude the analysis of the management of assembling inpatient medical records in hospitals From these journals, researchers obtained a sample of 16 journals. The results of the research showed that there were several factors in managing assembly in hospitals, namely: 40% of hospitals did not use medical record SOPs according to established regulations, 73% of medical record files were still incomplete in hospitals, 73% of medical record files were returned to the medical records room. in hospitals it is still not on time 100%, and the factor that causes Assembling not to be in accordance with SOPs using Fishbone theory which has the most influence is the Man factor which is related to the lack of discipline of Medical Records officers in hospitals as much as 100%.